Pemanfaatan ICT Sebagai Media atau Teknologi terhadap Pelaku Industri Rumahan untuk Memajukan Usahanya Melalui Layanan Bimbingan dan Konseling - Muhammad Fauzi Hasibuan; Safrizal Efendi; Minar Adelina (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2019)
Communication Information Technology (ICT) can be an effective tool for small and medium business communities to expand their business. Content Mastery Services are a support service to individuals to master certain abilities or competencies through learning activities. In this case the community is given mastery to have competence in marketing its home industry by using ICT. The Training of Trainner (TOT) method by means of providing materials through the content services in guidance and counseling, followed by a direct practice by the home industry actors. The results of this community service show that content Mastery Services is effective in delivering training content in ICT utilization for home industry players to advance their business.